Advancing autonomous navigation: YOLO-based road obstacle detection and segmentation for Bangladeshi environments - Mahmud, Ishtiaque; Ritu, Sumaia Arefin; Mahmood, Zaki Zawad (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.